Strategi Tax Center Fisip dalam Meningkatkan Kepatuhan Perpajakan di Lingkungan UIN Sunan Gunung Djati Bandung - Novia Irnawati; Safira Hamida; Rafli Firmansyah (UIN Sunan Gunung Djati Bandung, 2023)
Tax awareness in Indonesia still needs attention, one of which is in the university environment. The Tax Center carries out programs, such as annual SPT reporting assistance and tax education, to increase understanding and awareness of taxpayers regarding tax rights and obligations. This research was conducted using a descriptive method in a qualitative approach. A qualitative process was carried out by observation, interviews, and document studies to obtain data relevant to the research topic. Retrieval of informants for interviews using a purposive sampling technique. The results showed that the Tax Center of FISIP UIN Sunan Gunung Djati Bandung, through its programs, had increased public awareness and concern for taxation rights and obligations, as evidenced by the tax inclusion award and becoming Indonesia's 3rd best tax centre. The Tax Center received a positive response from the academic community, as seen from the student's interest in involvement as Tax Center administrators